1993
DOI: 10.1111/j.1365-2184.1993.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered cell‐cycle traverse of the non‐modal cells of the heteroploid MCa‐11 line

Abstract: Classic stem cell theory states that the growth of heteroploid cell populations is due to the proliferation of 'main stemline' cells with modal DNA content and chromosome number. Cells with non-modal DNA content and chromosome number are thought to be blocked and/or destroyed at mitosis. To test this, we studied two chromosomally stable cell populations (mouse bone marrow and WCHE-5 cells) and one heteroploid, chromosomally diverse cell line (MCa-11). The heteroploid MCa-11 cells showed significant [3H]dT labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…38 A subsequent study demonstrated that nonmodal cells were capable of continued cell proliferation but were delayed temporarily in the G 2 and/or the prophase-metaphase stages of the cell cycle relative to cells with a modal DNA content. 39 Our data support this hypothesis in that the informational content of the diploid or pseudo-diploid cells of the tumorigenic populations obviously differs from that of the diploid cells of the nontumorigenic founding population of WB-F344 cells. Chemical transformants of WB-F344 cells often contained a diploid or near-diploid DNA content by flow cytometry but exhibited chromosomal aneuploidy by karyotypic analysis.…”
Section: Discussionsupporting
confidence: 79%
“…38 A subsequent study demonstrated that nonmodal cells were capable of continued cell proliferation but were delayed temporarily in the G 2 and/or the prophase-metaphase stages of the cell cycle relative to cells with a modal DNA content. 39 Our data support this hypothesis in that the informational content of the diploid or pseudo-diploid cells of the tumorigenic populations obviously differs from that of the diploid cells of the nontumorigenic founding population of WB-F344 cells. Chemical transformants of WB-F344 cells often contained a diploid or near-diploid DNA content by flow cytometry but exhibited chromosomal aneuploidy by karyotypic analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Its presence has been correlated with a high risk of recurrences and metastases 56,57 . Aneuploid cells are able to complete mitosis regardless of chromosome number or DNA content although with a prolonged mitotic time 58 . From this point of view, the bad prognostic value of a high mitotic index could be because of a prolonged mitotic duration and not to an increase in the proportion of cells in mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Aneuploid cells are able to complete mitosis regardless of chromosome number or DNA content although with a prolonged mitotic time. 58 From this point of view, the bad prognostic value of a high mitotic index could be because of a prolonged mitotic duration and not to an increase in the proportion of cells in mitosis. As mitosis reflects a small proportion of the cell cycle, longer mitosis duration has little impact on the cell cycle time and therefore on MIB-1 staining.…”
Section: The Mib-1 Indexmentioning
confidence: 99%